Sodium Acetate Responses in Saccharomyces cerevisiae and the Ubiquitin Ligase Rsp5 - Watcharawipas, Akaraphol; Watanabe, Daisuke; Takagi, Hiroshi (Frontiers in Microbiology, 2018)
Recent studies have revealed the feasibility of sodium acetate as a potentially novel inhibitor/stressor relevant to bioethanol production from neutralized lignocellulosic hydrolysates. This mini-review focuses on subjects related to the nature of sodium acetate toxicity and its cellular responses, particularly via the high-osmolarity glycerol (HOG) pathway, the Rim101 pathway, the P-type ATPase sodium pumps Ena1/2/5, and the ubiquitin ligase Rsp5 with its adaptors. Increased understanding of cellular responses to sodium acetate would improve our understanding of how cells respond not only to different stimuli but also to composite stresses induced by multiple components simultaneously. Moreover, uncovering the nature of specific industrially-related stress conditions and their cellular responses would be a key step in the breeding of industrial yeast strains beneficial for the increasing production of bioethanol, advanced biofuels, and other chemicals that will be in demand in the coming era of bio-based industry.